PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PT. VICTORY RETALINDO CABANG CIKARANG) - Desi Julianingsih; Inna Nisawati (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
This study aims to determine whether there is a significant influence ofLeadership Style, Organizational Culture, and Organizational Commitment on Employee Performance at PT. Victory Retalindo Cikarang branch. With the population and sample in this study as many as 70 respondents. What needs to be known is that human resources are an important factor that is always in the company because to achieve a company's vision by carrying out the mission is basically governed by humans. Including companies in the retail sector, namely PT. Victory Retalindo Cikarang branch. Leadership style is a pattern of behavior of a typical leader when influencing his subordinates, what the leader chooses to do. Organizational culture is a system of values, norms and beliefs shared by a group of people in an organization that differentiates it from the others. Organizational commitment is where employees are very interested in the goals, values, and goals of the organization. Employee Performance is the ability, skills, and work results shown by an employee in carrying out their duties and responsibilities at work.The results of the R2 test which was carried out to test how much influence the independent variables had on the dependent variable in this study showed a figure of 87.7% while the other 12.3% were influenced by other factors. Leadership Style (X1) partially affects Employee Performance (Y) with a significance value of 0.007 or less than 0.05 and is declaredacceptable. Organizational Culture Variable (X2) partially affects Employee Performance (Y) with a significance value of 0.000 or less than 0.05 and is declared accepted. Organizational Commitment (X3) partially affects Employee Performance (Y) with a significance value of 0.000 or less than 0.05 and is declared accepted. Simultaneously the variables Leadership Style (X1), Organizational Culture (X2), Organizational Commitment (X3) have a positive effect on Employee Performance (Y) with a significance value of 0.00 or less than 0.05.